2009
DOI: 10.1159/000214221
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Circle of Willis: A Longitudinal Observation of Flow Patterns in the Circle of Willis One Week after Stenting for Severe Internal Carotid Artery Stenosis

Abstract: Background and Purpose: The purpose of the present study was to assess whether the direction of flow via the circle of Willis (CoW) changed after stenting for severe internal carotid artery (ICA) stenosis. Methods: 65 patients (38 men, mean age 63.2 ± 8.4 years, range 44–82) with a symptomatic ICA occlusion were investigated. Magnetic resonance angiography was performed prior to and 1 week after carotid artery stenting (CAS). The pattern in the CoW was assessed. Results: One third of the subjects (35.38%) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…In our previous study, 23 of 65 (35%) patients with symptomatic CAS had a significantly altered flow pattern in the circle of Willis on the magnetic resonance (MR) angiography after carotid artery stenting [19]. In summary, segments in the circle of Willis were opened preoperatively but blocked after carotid revascularization in 14 patients, whereas other segments of the circle of Willis were closed initially but reopened postoperatively in 9 patients, leading to the reorganization of Willisian collateralization.…”
Section: Dynamic Behavior Of Collateral Flow After Carotid Revascularmentioning
confidence: 90%
“…In our previous study, 23 of 65 (35%) patients with symptomatic CAS had a significantly altered flow pattern in the circle of Willis on the magnetic resonance (MR) angiography after carotid artery stenting [19]. In summary, segments in the circle of Willis were opened preoperatively but blocked after carotid revascularization in 14 patients, whereas other segments of the circle of Willis were closed initially but reopened postoperatively in 9 patients, leading to the reorganization of Willisian collateralization.…”
Section: Dynamic Behavior Of Collateral Flow After Carotid Revascularmentioning
confidence: 90%
“…Bu oran normal popülasyonda için bildirilmiş olan yaklaşık %50 oranına göre yüksektir. Fakat normal popülasyondaki anomalik WP segment sıklık sırası ile bizim olgularımız arasında belirgin fark yoktu (14,16) WP anomalilerinden hangisinin hemodinamik yetmezlikte önemli olacağı tutulum konfigürasyonuna göre değişir. Örneğin P1 segmentinin aplazisi yada çapının PcomA' den daha küçük olması durumunda oksipital lobun kan ihtiyacı PcomA vasıtasıyla ipsilateral İKA' dan sağlanacağından (17), ipsilateral hemisferin perfüzyonunda bozukluk ortaya çıkacak bu da artmış inme riskine neden olacaktır.…”
Section: Discussionunclassified
“…Radiosurgery reduced the collateralization demand, which shut down recruitment and led to a false-positive MRA diagnosis of CoW vascular hypoplasia. CoW segmental hypoplasia is not only a variable feature, but is also enrolled as part of an autoregulatory mechanism [3,4]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the collateral pathway may be reversely closed after pathological hemodynamics have been corrected. One of our previous studies found that extracranial internal carotid artery occlusion might lead to a prompt initiation of CoW collaterals, while they promptly ceased in one third of the subjects after carotid artery stenting [3]. However, the number of blocked recruiting segments in the CoW was statistically higher than that of ‘hypoplastic’ segment openings in the CoW.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation